Fungicide Efficacy Against Botrytis cinerea at Different Positions on Grape Shoots - van Rooi, C.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Fungicide efficacy at different positions on grape shoots was determined on vinelets inoculated with Botrytis cinerea. To ensure proper fungicide coverage, vinelets (table grape cultivar Dauphine, wine grape cultivar Merlot noir), prepared from cuttings, were sprayed in a spray chamber at the recommended dosages with iprodione, pyrimethanil, cyprodinil/fludioxonil  and fenhexamid. Vinelets for the control treatment were left unsprayed.   After 24 h the vinelets were dusted with dry, airborne conidia in a settling ower to reduce the sporadic occurrence of the pathogen on shoots and incubated for 24 h at high relative humidity (±93 % ) to promote infection.  Fungicide efficacy was determined by observing intact vinelets for symptom expression at nodes, internodes, leaf blades, petioles and inflorescences, and by determining surface colonisation (shoots left unsterile) and penetration (surfacedisinfested shoots) by isolation studies. Symptoms of  B. cinerea decay did not develop on sprayed and unsprayed vinelets that  were kept in dry chambers during the 2-week observation period. The pathogen, however, developed from the isolated parts. On the unsprayed vinelets for both cultivars B. cinerea incidences recorded on two media and the two sterility regimes were significantly higher on leaf blades than on the petioles, shoot pieces and inflorescences. The isolation studies showed that the different fungicides were highly and nearly equally efficient in reducing superficial B. cinerea and latent infection at the various positions. In the  case of leaf blades B. cinerea incidence was significantly reduced by each fungicide on both cultivars. This was not the case for the other parts, which yielded B. cinerea at low incidences under the two sterility regimes. The study showed that the fungicides used in this study, if applied properly to shoots at the pre-bloom stage, should effectively reduce the amount of B. cinerea in leaves and completely prevent the infection of nodes, internodes and inflorescences.